The Effect of Make a Match Learning Models and Cognitive Ability to Recognize the Concept of Number - Siti Rahmatunnisa; Anita Yus; Evi Eviyanti (BIRCU, 2020)
This study aims to investigate: (1) the difference of ability to recognize the concept of numbers between children taught by Make a Match learning model based on creativity and children taught by Make a Match learning model; (2) the difference of ability to recognize the concept of numbers between children who have high cognitive abilities and low cognitive abilities, and (3) the interaction between Make a Match learning model with children's cognitive abilities on the ability to recognize concepts. The sample in this study is 28 children in class B1 for the experimental class who are taught by Make a Match based on creativity and for the control class, class B2 consisted of 28 children who were taught by Make a Match. They are 5-6 years old children at Raudhatul Athfal Mutiara Bunda Banda Aceh. The results show that: (1) The ability of children who taught by Make a Match learning model based on creativity is 44.96, it is higher than children who taught by Make A Match learning, it is 34.64, (2) The ability to recognize the number concept of children who have high cognitive abilities obtained an average value of = 46.89, while children who have low cognitive abilities obtained an average value of = 33.21, and (3) The results show that there was no significant interaction between the use of learning and children's cognitive abilities (high and low) in influencing the ability to recognize the concept of numbers.